Redefining Gender Equality: A Senegalese Conversation with Islam - Seulgie Lim (Africa Spectrum)
How do Muslim women balance their religious agency and political aspirations? Gender quotas have been used across the African continent to improve women's political visibility since the 1990s. Senegal's own experiment with gender equality in 2010 faced political barriers as well as religious ones. The author sheds light on how Muslim women activists in Senegal shaped women's place in their communities through the gender parity law. Based on multiple fieldwork visits from 2016 to 2018 and individual interviews with activists and scholars involved in the movement to make gender parity the law in Senegal, the author argues that while Islam may not always be the most adequate tool to dismantle patriarchal norms, it remains a valuable framework for women activists in Senegal to achieve secular change.